2004
DOI: 10.4049/jimmunol.172.8.4956
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Receptor Expressed on Myeloid Cells-1 in Neutrophil Inflammatory Responses: Differential Regulation of Activation and Survival

Abstract: Polymorphonuclear neutrophils (PMN) are crucial in the innate host defense by their ability to rapidly accumulate in inflamed tissues and clear a site of infection from microbial pathogens by their potent effector mechanisms. The triggering receptor expressed on myeloid cells (TREM)-1 is a recently described activating receptor on PMN with an important role in inflammation. However, the effects of TREM-1 stimulation on a cellular level remain to be further defined. To characterize TREM-1-mediated activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
177
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(196 citation statements)
references
References 36 publications
15
177
1
3
Order By: Relevance
“…CD300e ligation induced a rapid intracellular calcium mobilization, as well as the production of ROS, supporting that this receptor may regulate the microbicidal activity of monocytes [33]. Similarly, and in line with the previous reports on the ability of both hOSCAR and TREM-1 to trigger the respiratory burst in granulocytes [27,34], we have observed that TREM-1 activates ROS production also in monocytes.…”
Section: Discussionsupporting
confidence: 91%
“…CD300e ligation induced a rapid intracellular calcium mobilization, as well as the production of ROS, supporting that this receptor may regulate the microbicidal activity of monocytes [33]. Similarly, and in line with the previous reports on the ability of both hOSCAR and TREM-1 to trigger the respiratory burst in granulocytes [27,34], we have observed that TREM-1 activates ROS production also in monocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Activation of TREM-1 is associated with release of proinflammatory mediators and reactive oxygen and nitrogen intermediates by phagocytic leukocytes (Bouchon et al, 2000;Gibot et al, 2007;Radsak et al, 2004). These activities have been linked to hepatotoxicity (Jaeschke and Hasegawa, 2006;Laskin and Laskin, 2001;Laskin and Pendino, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…5A) and also did not promote neutrophil activation as measured by upregulation of cell surface levels of the adhesion molecule CD66b (Supplemental Fig. 5B) (45). IDR-1002 also did not affect the in vitro viability of human neutrophils at concentrations up to 125 mg/ml (Supplemental Fig.…”
Section: Effects Of Idr-1002 On Microbicidal Activities Of Leukocytesmentioning
confidence: 99%